Cost-effectiveness of insulin detemir versus insulin glargine for Thai type 2 diabetes from a payer’s perspective - Unchalee Permsuwan (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Aims: An economic evidence is a vital tool that can inform the decision to use costly insulin analogs. This study aimed to evaluate long-term cost-effectiveness of insulin detemir (IDet) compared with insulin glargine (IGlar) in type 2 diabetes (T2DM) from the Thai payer’s perspective. Methods: Long-term costs and outcomes were projected using a validated IMS CORE Diabetes Model, version 8.5. Cohort characteristics, baseline risk factors, and costs of diabetes complications were derived from Thai data sources. Relative risk was derived from a systematic review and meta-analysis study. Costs and outcomes were discounted at 3% per annum. Incremental cost-effectiveness ratio (ICER) was presented in 2015 US Dollars (USD). A series of one-way and probabilistic sensitivity analyses were performed. Results: IDet yielded slightly greater quality-adjusted life years (QALYs) (8.921 vs 8.908), but incurred higher costs than IGlar (90,417.63 USD vs 66,674.03 USD), resulting in an ICER of ∼1.7 million USD per QALY. The findings were very sensitive to the cost of IDet. With a 34% reduction in the IDet cost, treatment with IDet would become cost-effective according to the Thai threshold of 4,434.59 USD per QALY. Conclusions: Treatment with IDet in patients with T2DM who had uncontrolled blood glucose with oral anti-diabetic agents was not a cost-effective strategy compared with IGlar treatment in the Thai context. These findings could be generalized to other countries with a similar socioeconomics level and healthcare systems.